Fabrication and characterization of zein/bioactive glass deposited on pretreated magnesium via electrophoretic deposition - Ahmed, Yusra; Nawaz, Aneeqa; Virk, Ranjot; Wadood, Abdul; Ur Rehman, Muhammad Atiq (International Journal of Ceramic Engineering & Science, 2020)
In this study, zein/45S5 bioactive glass (BG) coatings were deposited via electrophoretic deposition (EPD) on pretreated pure magnesium (Mg) substrates to control the rapid degradation of magnesium and to improve the bioactive properties of Mg implants. The EPD parameters were first optimized on stainless steel (SS), and then, the optimum EPD parameters were applied to obtain zein/BG composite coatings on Mg substrates. The kinetics of the EPD process was studied by plotting the graph between current density and deposition time at fixed applied voltage. The morphology and chemical composition (qualitatively) of the obtained coatings were studied by scanning electron microscopy (SEM) and Fourier-transformed infrared spectroscopy (FTIR), respectively. SEM and FTIR results showed that both zein and BG were successfully deposited, and a homogeneous film of zein/BG was formed on the surface of the substrate. The contact angle measurements confirmed that the zein/BG coatings are suitable for the initial protein attachment.
CRIS-Team Scopus Importer:2024-12-16
Keywords: bioactivity glass; electrophoretic deposition; Magnesium; Zein